Optimization of extraction parameters of selected Malaysian plants towards antiurolithiatic activities (IN-VITRO) - Abdul Rahim, Nur Fazira (2021)
Urolithiasis has become a worldwide problem and its management depends on surgical procedures that are costly and cause reoccurrence. Anacardium occidentale (gajus), Ananas comosus (nanas), Aquilaria malaccencis (karas), Centella asiatiaca (pegaga), Ceiba petandra (kekabu), Euphorbia hirta (ara tanah), Ficus carica (ara), Melastoma malabthricum (senduduk), Piper sarmentosum (kaduk) and Tradescantia zebrina (kura-kura air) have been used traditionally to treat urolithiasis. However, no scientific data has been recorded on the extraction parameters. Thus, the objective of this study is to assess for the best ethnobotanical plant extract with good antiurolithiatic properties, followed by optimization of extraction parameters of selected plant extracts. The antiurolithiatic activities conducted were turbidity and titrimetric assays (in-vitro). Ethnobotanical plant extracts assessment revealed A. occidentale and A. malaccencis had the best antiurolithiatic activities as both plants had no significant difference with standard drugs (p>0.05). The extraction parameters studied were solvent concentration, extraction temperature and time that was screened using two-level factorial design and optimized by response surface methodology and central composite design. The results showed that optimum extraction condition for A. occidentale extract (0.4% ethanol, 31.5°C, 30 minutes) on both antiurolithiatic activities were exhibited 85.57±0.43% (turbidity) and 96.48±0.70% (titrimetric). Meanwhile, optimum condition of A. malaccencis extract (100% ethanol, 30.0°C, 30 minutes) demonstrated 83.58±0.75% (turbidity) and 86.57±0.80% (titrimetric). Phenols, alkaloids, saponins, flavonoids, tannins and terpernoids were identified in both optimized extracts and all have positive correlation on both antiurolithiatic assays except flavonoids. Toxicity testing using brine shrimp lethality assay presented non-toxic effect on optimized A. occidentale (LC50, 1412.50μg/mL) but A. malaccencis (LC50, 30.50μg/mL) revealed toxic effects. This study has given basic scientific evidence that optimum extraction condition is necessary to obtain optimum antiurolithiatic activity.